Wnt controls the medial–lateral subdivision of the Drosophila head. (25th July 2018) - Magri, M. S.; Domínguez-Cejudo, M. A.; Casares, F.
Abstract : In insects, the subdivision of the head into a lateral region, harbouring the compound eyes (CEs), and a dorsal (medial) region, where the ocelli localize, is conserved. This organization might have been already present in the insects' euarthropodan ancestors. In Drosophila, the Wnt-1 homologue wingless (wg) plays a major role in the genetic subdivision of the head. To analyse specifically the role of wg signalling in the development of the dorsal head, we attenuated this pathway specifically in this region by genetic means. We find that loss of wg signalling transforms the dorsal/medial head into lateral head structures, including the development of ectopic CEs . Our genetic analysis further suggests that wg signalling organizes the dorsal head medial–lateral axis by controlling, at least in part, the expression domains of the transcription factors Otd and Ey/Pax6.